Characterization of the complete chloroplast genome of the medicinal plant Orixa japonica (Rutaceae) in Zhejiang Province and its phylogenetic analysis within family Rutaceae. Issue 6 (3rd June 2021) - Ying, Zhiqi; Yan, Meixiu; Zhou, Manjia; He, Xiangyu; Cheng, Rubin
Abstract: Orixa japonica Thunb. is an important medicinal plant belonging to the family Rutaceae. In this study, we determined the the complete chloroplast (cp) genome of O. japonica, which was 158, 525 bp in length containing one large single copy region (85, 965 bp), one small single copy region (18, 552 bp), and a pair of inverted repeat regions (27, 004 bp each). A total of 134 genes were annotated in the cp genome, including 88 protein coding genes, 37 tRNA genes, eight rRNA genes, and one pseudo gene ycf1. According to the phylogenetic analysis, O. japonica clustered together with Casimiroa edulis with high bootstrap value, indicating a close genetic relationship with subfamily Amyridoideae.